Nickel-Mediated Synthesis of Isoindolinones at Room Temperature - Wertjes, William C.; Waller, Peter J.; Shelton, Kyle E.; Kalyani, Dipannita (Synthesis, 2014)
This communication describes a method for the Ni(cod)2-mediated intramolecular arylation of alkyl C−H bonds adjacent to the nitrogen atom in benzamide substrates. The transformation proceeds at room temperature and exhibits selectivity for functionalization of more substituted C−H bonds. The yields of the desired isoindolinone products are higher with benzamide substrates containing tertiary alkyl groups on the nitrogen atom than with those bearing primary or secondary alkyls. The results described herein suggest a mechanism involving radical intermediates for these reactions.
Keywords: amides; arylation; intramolecular; nickel; halides